2017
DOI: 10.31018/jans.v9i2.1328
|View full text |Cite
|
Sign up to set email alerts
|

Role of Information and communication technology (ICT) in agriculture and extension

Abstract: Information and communication technology (ICT) aids provide up-to-date information on the market prices of commodities, inputs and consumer trends which ultimately can improve a farmer's negotiating position and their livelihood. Major aspect of ICT is that accurate information should reach the farmers at the right time to make more sustainable use of on-farm resources. Now the question arises that how this information can be disseminated to such a diverse group of the farming community. ICT is going to play g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Due to the worldwide scarcity of water in the world, information technology and water experts around the world have combined forces to explore solutions through ICTS. Hydro-informatics systems use simulation modelling to solve problems of hydraulics, hydrology, and environmental engineering to better manage water systems (Rohila et al, 2017). The information gathered is combined and conveyed using interactive graphs, videos, pictures, and audios.…”
Section: Use Of Icts In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the worldwide scarcity of water in the world, information technology and water experts around the world have combined forces to explore solutions through ICTS. Hydro-informatics systems use simulation modelling to solve problems of hydraulics, hydrology, and environmental engineering to better manage water systems (Rohila et al, 2017). The information gathered is combined and conveyed using interactive graphs, videos, pictures, and audios.…”
Section: Use Of Icts In Agriculturementioning
confidence: 99%
“…Complete reports can be published as hardcopies or soft copies. ICTS is used for the promotion, marketing, transmission and sharing of the reports and drives as well as cloud are used to store the information for later use (Rohila, Yadav and Ghanghas, 2017).…”
Section: Use Of Icts In Agriculturementioning
confidence: 99%
“…Therefore, training programs should be organized to overcome the constraints along with to provide infrastructure facilities, resources, tools and internet (Albert, 2014). While Rohila et al (2017) suggested that low cost ICT tools such as mobile phones etc. should be promoted to provide agricultural information.…”
Section: Constraints In Adoption Of Information and Communication Technologies (Icts)mentioning
confidence: 99%
“…It is estimated that almost 60% of the farmers lack access to information on advanced technologies [18]. The information and communication technologies (ICTs) are increasingly becoming popular to provide customised and accurate information to the farmers in a time-bound manner [19]. The usage of smartphones and availability of internet at affordable prices offered ways to solve such dilemma of farmers through mobile apps.…”
Section: Introductionmentioning
confidence: 99%